The Critical Role of Soft Skills in Engineering: Enhancing Performance and Career Advancement - Ibrahim, Irmohizam; Abiddin, Norhasni Zainal (Journal of Ecohumanism, 2024)
Today’s engineering graduates seeking jobs require a combination of technical abilities and the right soft skills, as organizations prefer a professional individual who has developed an overall personality that encompasses both professionalism and alignment with society, rather than relying solely on qualifications and academic scores. The 21st-century workforce has changed the way they define job skills, with managers prioritizing non-technical (soft) skills in addition to technical skills, as having these alone is no longer enough in today’s competitive market place. This article aims to analyze the significance of soft skills in the engineering sector, as highlighted in the literature review. An understanding of these soft skills is crucial for organizations to optimize the levels of productivity amongst their employees and for individuals desiring to advance their futures within a competitive job landscape. This article attempts to shed light on these soft skills in the hopes of investing in training program designs that can maximize engineers professional efficacy and career successes within their industry, engineering.